Development of women entrepreneurship in India: a study of public policies and programmes - Chandra, Shanta Kahli (New Delhi, 1991)
Women make half the human resource potential available for economic activity. There is a realisation that full involvement of women in industrial development would ensure effective utilisation of labour and improve quality of life. This leads to the presumption that action must be taken by the government to analyse current status and potential role of women in the process of industrialisation. The issue of women in the industrialisation process has attracted attention of the government only in the last decade. The present book is based on the study of women entrepreneurs and effectiveness of public policies and services available to them. As there is need to secure fair share for women in employment opportunity and increase rate of participation by them in the work force, the present study is timely and informative. The field data throw light on the problems faced by women entrepreneurs and suggest some solutions to the problems.
Keywords: Entrepreneurship-Women